Faktor-Faktor yang Mempengaruhi Price Earning Ratio - Agung Septian; Tri Bodroastuti (Jurnal Ilmiah Aset, 2014)
PER (price earnings ratio) is a very important factor and should be considered by investors before making an investment decision. The purpose of this study was to determine the effect of Earning Per Share, Return on Assets, Return on Equity, Debt To Equity Ratio, and Price Book Value for the price earning ratio (PER) of Automotive and Allied Products Companies listed in Indonesia Stock Exchange in 2009-2011. The populations in this study were the Automotive and Allied Products companieslisted in Indonesia Stock Exchange amounted to 17 (seventeen) companies. The sampling technique was conducted with purposive sampling method and acquired 16 companies as the study sample. The data analysis technique used was linear regression. Based on the results of the regression analysis showed that Earning Per Share, Return on Assets, and Debt To Equity Ratio had no significant effect on the price earning ratio (PER). While Return On Equity had positive effect on the price earning ratio (PER) and Price Book Value negatively affected the price earning ratio (PER) in Automotive and Allied Products Companies listed in Indonesia Stock Exchange in the period 2009-2011.